2021
DOI: 10.1159/000513066
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Sub-Classification of Atypia of Undetermined Significance May Predict Malignancy Risk in Thyroid Nodules

Abstract: <b><i>Background:</i></b> Atypia/follicular lesion of undetermined significance (AUS/FLUS) carries a malignancy risk reaching up to 50%. Based on the reported malignancy rate in a given population, the clinical practice towards such a category varies. We hereby identify clinical parameters for risk stratification to aid in decision-making for either surgical referral or a clinical follow-up. Our aim is to identify clinical parameters that guided both clinicians and patients at our insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre‐operative information for malignant nodules 10,11,15,16 . However, a notable portion of nodules remained as AUS after repeat aspiration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre‐operative information for malignant nodules 10,11,15,16 . However, a notable portion of nodules remained as AUS after repeat aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…2 In more recent years, molecular testing incorporated with FNA evaluation has played an important role in further stratification and management of indeterminate thyroid nodules. 6,7 Among several commercially available tests, the Afirma Genomic Sequencing Classifier (GSC) was introduced in 2017, and uses next-generation sequencing, incorporating an ensemble model composed of 12 independent classifiers (10,196 genes with 1115 core genes) and 7 other components (parathyroid, medullary thyroid carcinoma, BRAFV600E, RET/PTC1 and RET/PTC3 detection modules, oncocytic cell index and oncocytic neoplasm index). Compared with its predecessor, the Gene Expression Classifier (GEC), the newer GSC has demonstrated improved specificity and positive predictive value (PPV) while maintaining a high sensitivity and negative predictive value (NPV).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROM of AUS/FLUS diagnosis according to TBSRTC (2017) is estimated to be 10–30% if noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) is considered malignant, and 6–18% if excluding NIFTP from the malignant group [ 3 , 4 ]. However, some authors suggest higher malignancy risk, reaching up to 50% [ 10 ], and even after excluding NIFTP [ 11 ]. Based on the various ROM rates, the clinical practice towards AUS/FLUS category varies.…”
Section: Discussionmentioning
confidence: 99%